Introducing Education for Sustainable Development in Emerging Economies - Aditya (JOURNAL OF INDIAN EDUCATION, 2018)
The vulnerable population in emerging economies is more prone to the adverse impacts of climate change. Urgent need is felt for sensitising people towards the effects of climate change, its mitigation and ways to become resilient. This paper argues for introducing Education for Sustainable Development (ESD) in emerging economies as a potent action. The paper has argued for embedding ESD across subjects and school curricula. It should be given a cross-curricula priority. Secondly, as a teacher plays a crucial role in the above process, there is a need to ensure that teachers have proper knowledge of the subject and are aware of the different pedagogies to transact and equip with required competencies. Thirdly, contextualisation of education can help students to relate to sustainable practices. Last but not the least, activity and project-based approach could be used to motivate students to adopt a sustainable lifestyle.